The impact of community health workers on antenatal and infant health in India: A cross-sectional study - Pranay Nadella; S.V. Subramanian; Andres Roman-Urrestarazu (Elsevier, 2021)
Background: Community health workers (CHWs) are central to India's strategy for reaching the Sustainable Development Goals around maternal and child health. Despite India's significant investment in these programs, few studies have analyzed the effect of CHWs across India. Objective: This study aims to analyze multiple types of CHWs and their impact on a broad range of antenatal and infant health outcomes across India. Methods: In this population-based cross-sectional study, we analyzed data of women interviewed by the most recent 2015-2016 National Family Health Survey-4 (NFHS-4) in India. This study performed multiple variable regressions to examine the effect of receiving ANC during pregnancy from 1) any CHW and 2) by specific type of CHW - Accredited Social Health Activist (ASHA), Anganwadi Worker (AWW), and Community/Village Health Worker (defined in Table 1) on antenatal and infant health outcomes. Results: Of 166,498 women, 14.2% received ANC from any CHW with specifically 5.9% receiving from ASHAs, 10.2% receiving from AWWs, and 0.5% receiving from Community/Village Health Workers. Women who received ANC from an ASHA had increased ANC utilization (OR 1.77; 95% CI 1.65, 1.91) as well as quality (IRR 1.06; 95% CI 1.05, 1.08), increased early initiation of breast feeding (OR 1.20; 95% CI 1.12, 1.29), and decreased one-year mortality (OR 0.75; 95% CI 0.63, 0.88). Women who received ANC from an AWW had increased ANC utilization (OR 2.24; 95% CI 2.12, 2.37) as well as quality (IRR 1.07, 95% CI 1.06, 1.08) and increased early initiation of breast feeding (OR 1.30; 95% CI 1.26, 1.40). Conclusion: Receiving ANC from ASHAs and AWWs is associated with improved ANC utilization, ANC quality, early initiation of breastfeeding and the key outcome of reduced infant mortality.